Automatic verification of competitive stochastic systems - Simaitis, A (2014)
In this thesis we present a framework for automatic formal analysis of competitive stochastic systems, such as sensor networks, decentralised resource management schemes or distributed user-centric environments. We model such systems as stochastic multi-player games, which are turn-based models where an action in each state is chosen by one of the players or according to a probability distribution. The specifications, such as “sensors 1 and 2 can collaborate to detect the target with probability 1, no matter what other sensors in the network do” or “the controller can ensure that the energy used is less than 75 mJ, and the algorithm terminates with probability at least 0.5'', are provided as temporal logic formulae. We introduce a branching-time temporal logic rPATL and its multi-objective extension to specify such probabilistic and reward-based properties of stochastic multi-player games. We also provide algorithms for these logics that can either verify such properties against the model, providing a yes/no answer, or perform strategy synthesis by constructing the strategy for the players that satisfies the specification. We conduct a detailed complexity analysis of the model checking problem for rPATL and its multi-objective extension and provide efficient algorithms for verification and strategy synthesis. We also implement the proposed techniques in the PRISM-games tool and apply them to the analysis of several case studies of competitive stochastic systems.